Highly Selective Production of Ethylene by the Electroreduction of Carbon Monoxide. (3rd December 2019) - Chen, Ruixue; Su, Hai‐Yan; Liu, Deyu; Huang, Rui; Meng, Xianguang; Cui, Xiaoju; Tian, Zhong‐Qun; Zhang, Dong H.; Deng, Dehui
Abstract: Conversion of carbon monoxide to high value‐added ethylene with high selectivity by traditional syngas conversion process is challenging because of the limitation of Anderson‐Schulz–Flory distribution. Herein we report a direct electrocatalytic process for highly selective ethylene production from CO reduction with water over Cu catalysts at room temperature and ambient pressure. An unprecedented 52.7 % Faradaic efficiency of ethylene formation is achieved through optimization of cathode structure to facilitate CO diffusion at the surface of the electrode and Cu catalysts to enhance the C−C bond coupling. The highly selective ethylene production is almost without other carbon‐based byproducts (e.g. C1 –C4 hydrocarbons and CO2 ) and avoids the drawbacks of the traditional Fischer–Tropsch process that always delivers undesired products. This study provides a new and promising strategy for highly selective production of ethylene from the abundant industrial CO. Abstract : CORTE in the act : Ein direkter elektrokatalytischer Prozess ermöglicht eine hochselektive CO‐Reduktion zu Ethylen (CORTE) mit Wasser über Cu‐Katalysatoren bei Raumtemperatur und Umgebungsdruck. Ein beispielloser Faradayscher Wirkungsgrad (FE) für die Ethylenbildung von 52.7 % resultiert aus der Optimierung der Kathodenstruktur, um die CO‐Diffusion zu erleichtern.